Unveiling Moebius Syndrome: Understanding the Rare Neurological Condition - Duthan, Sarath; Jayakrishnan, S S; Sajitha, G; Sajna, S J (Indian Journal of Pharmacy Practice)
Moebius Syndrome is a rare congenital neurological disorder that affects the sixth and seventh cranial nerves, leading to facial paralysis, impaired eye movement and other associated symptoms. The exact etiology of Moebius Syndrome is not fully understood, but genetic factors, exposure to toxins during fetal development, vascular anomalies or acquired ischemia events have been proposed as potential contributing factors. Clinical manifestations include unilateral or bilateral nonprogressive congenital facial palsy, deficiencies in ocular abduction and limb abnormalities, among other cranial nerve palsies. It is primarily clinical, as there are no specific laboratory tests available for evaluation. Pharmacological management for Moebius Syndrome is limited, and there is no specific pharmaceutical treatment available. Multivitamins may be added to the treatment regimen. Surgical methods, such as the "smile operation," temporalis tendon transfer and bilateral selective neurolysis can be used to correct lagophthalmos and strabismus. Children with Moebius Syndrome can live almost normal lives with the support of a multidisciplinary team. Moebius Syndrome presents a unique set of challenges due to its rarity and the diverse range of symptoms it encompasses. Understanding its pathogenesis, clinical signs, diagnosis, and management is crucial for early diagnosis, intervention, and management to improve the quality of life for individuals affected by this condition.
Keywords: Congenital Neurological Condition; Cranial Nerve Dysfunction; Moebius Syndrome; Seventh Cranial Nerve; Sixth Cranial Nerve